Risk of anaemia in HIV positive pregnant women in Ibadan, Southwest Nigeria (2011)
Anaemia in pregnancy is an important cause of maternal and neonatal mortality. It is a recognized co-morbidity of HIV infection. This study aimed to determine the risk of anaemia in HIV positive pregnant women. Methodology- This is a cross sectional study of healthy pregnant women attending Adeoyo Hospital, a secondary health centre in South-western Nigeria over a 1- month period (January 2007). During the study period, 2,737 eligible women presented for antenatal care. About 98% (2,682) of these women consented to HIV testing. Over all, their mean (± S.D) packed cell volume was 30.96% (±4.13). The prevalence of HIV infection was 2.9% (95% Cl 2.3% - 3.6%) and the overall prevalence of anaemia was 33.1%. Frequency of anaemia was significantly higher in HIV +ve women (57.3% vs. 42.7%, p= 0.00. OR=2.81., CI=1.72-4.58). HIV +ve women presented more frequently with moderate or severe anaemia. In the logistic regression analysis only HIV infection (OR=2.4, 95%CI=1.37- 4.21) and primigravidity (OR=1.25,95% 0=1.04-15.2) remained independently associated with anemia. Anaemia is common in HIV positive pregnant women in this environment. Care providers must endeavor to determine the HIV status of every pregnant woman especially if she presents with anaemia with a view to providing appropriate interventions.